The Trans-Atlantic Slave Trade and the Evolution of Political Authority in West Africa - Warren C. Whatley (African Economic History Network (AEHN), 2013)
I trace the impact of the trans-Atlantic slave trade on the evolution of political authority in West Africa. I present econometric evidence showing that the trans-Atlantic slave trade increased absolutism in pre-colonial West Africa by approximately 17% to 35%, while reducing democracy and liberalism. I argue that this slavery-induced absolutism also influenced the structure of African political institutions in the colonial era and beyond. I present aggregate evidence showing that British colonies that exported more slaves in the era of the slave trade were ruled more-indirectly by colonial administrations. I argue that indirect colonial rule relied on sub-national absolutisms to control populations and extract surplus, and in the process transformed absolutist political customs into rule of law. The post-colonial federal authority, like the colonial authority before it, lacked the administrative apparatus and political clout to integrate these local authorities, even when they wanted to. From this perspective, state-failure in West Africa may be rooted in a political and economic history that is unique to Africa in many respects, a history that dates at least as far back as the era of the transatlantic slave trade.
Keywords: N37; N47; N57; 330; Africa; slavery; trade; political authority; rule of law